LOYALTY VALUE CONCEPT IN ENGLISH (Conferencea, 2024)
This article attempts to explore the expression of the concept of devotion in English and Uzbek languages, classify its usage, and examine the lexemes that represent the concept of devotion along with their semantic characteristics, differences in dictionaries, and their depiction in literary works, revealing their cultural specificity.